1997
DOI: 10.1038/sj.ejcn.1600406
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol beverage drinking, diet and body mass index in a cross-sectional survey

Abstract: Objective: The study was carried out to determine the associations of alcohol beverage drinking with macronutrients, antioxidants, and body mass index. Setting: Dietary subsample of the 1992 Finmonica cardiovascular risk factor survey in Finland; a cross-sectional study. Subjects: 985 women and 863 men were drawn from the population register in the four monitoring areas. All subjects were 25±64 y of age. Methods: The mailed questionnaire included questions covering socioeconomic factors, physical activity, smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 25 publications
7
67
1
Order By: Relevance
“…The common belief, supported by a number of epidemiological studies, is that drinking beer promotes abdominal fat distribution 14 and that wine, in contrast, has no effect 5 or is associated with lower WHR. 17 One limitation to these studies is that they were conducted in the US 14,17 or Finland, 5 where beer is a major source of alcohol and wine consumption is more prevalent in educated people. Such cultural and educational differences are likely to be important sources of confusion.…”
Section: Discussionmentioning
confidence: 99%
“…The common belief, supported by a number of epidemiological studies, is that drinking beer promotes abdominal fat distribution 14 and that wine, in contrast, has no effect 5 or is associated with lower WHR. 17 One limitation to these studies is that they were conducted in the US 14,17 or Finland, 5 where beer is a major source of alcohol and wine consumption is more prevalent in educated people. Such cultural and educational differences are likely to be important sources of confusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study suggested a J-shaped relationship, with the highest level of alcohol intake associated with an increase in BMI 2 . In men, some studies have not found any relationship between alcohol consumption and BMI 2,10,22 , but others showed either a positive association 12,19,23,24 or an inverse one 19,20 . A J-shaped relationship was reported in non-smoking men; non-drinkers and subjects with a daily intake $ 36 g dl 21 had a higher body weight than moderate drinkers 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of American people, BMI tended to increase with spirits intake in men only and was associated with neither beer nor wine 2 . In Finland, spirit drinkers were also shown to be heavier than other alcohol consumers 20 . In a cohort of Swedish women, BMI was inversely related to wine consumption, while beer and spirits did not show any significant relationships to BMI 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that, as ethanol is converted to acetate, the latter inhibits fat breakdown 14 . However, moderate ethanol drinkers (less than 50 g per day) actually show weight loss 13,20 . It is believed that ethanol induces an increase in the sensitivity of muscle to insulin with a down-regulation of the effect of insulin on adipose tissue, so fat mass decreases 19 .…”
Section: How the Body Deals With Ethanolmentioning
confidence: 99%